Mechanical Characterisation, Analysis and Modelling of Particulate Nanocomposites Printed Using Photopolymer Extrusion Technique - Asif, Muhammad (Auckland University of Technology, 2019)
A new photopolymer extrusion 3D printing technique is proposed in this research. This hybrid 3D printer combines the strengths of two well established and commercial 3D printers i.e. fused deposition modelling (FDM) and UV assisted 3D printing (UV3DP). One of the distinct features of this novel technique is its two additional rotational axes, which are installed to print free-form and self-supported structures. A detailed and comprehensive study is carried out in this research on the mechanical characterisation, analysis and modelling of particulate nanocomposites printed using photopolymer extrusion technique. Photopolymer resin is used as the base material in this technique. Generally, polymers are found to have low strength and stiffness. Nano sized fibres or particles are generally embedded in the polymer matrix to enhance their properties. Therefore, in order to improve the mechanical behaviour of the parts manufactured using photopolymer extrusion 3D printing technique, nano silica filler was added to the base material. Different concentrations of the silica filler were added and its effect on material viscosity, dimensional accuracy, strength and ductility have been studied. This part of the research outlined a suitable range of viscosities corresponding to different filler concentrations, provided plausible explanation on dimensional accuracy, reported significant improvement in mechanical properties of nanocomposite with the addition of the silica filler and demonstrated the capability of the proposed technique to print free-form and self-supported structures. Interfacial adhesion, i.e. the bond between matrix and nanoparticles is one of the major contributors to the strong mechanical properties of the particle reinforced polymers. A comparison of the interfacial adhesion was drawn between 3D printed and casted samples. This part of the research outlined with the aid of scanning electron microscopy, why nanocomposites printed using photopolymer extrusion technique have superior mechanical properties than casted samples. Polymers are viscoelastic materials and they exhibit time dependent response. To study the time dependent mechanical response of the photopolymer used in the proposed technique, tensile tests at different strain rates were conducted. Silica filler was added to enhance the mechanical properties of the polymer. Quasi linear viscoelastic (QLV) model combining hyper and viscoelastic phenomena was used to model the rate dependent mechanical behaviour of the polymer and polymer reinforced composite with different concentrations of the filler. This part of the research outlined that the addition of the silica enhanced the mechanical properties of the polymer. It also outlined that higher filler content could lead to weak mechanical properties. Furthermore, it showed that QLV model with Yeoh’s strain energy density function successfully captures the rate dependent stress-strain behaviour of the polymer and nanocomposite. Finite element modelling (FEM) is a powerful tool and is commonly used to predict the behaviour of polymer nanocomposites. A FE model was developed by combining hyper and viscoelastic phenomena to investigate the effect of filler concentration on mechanical behaviour of the 3D printed particulate nanocomposite. The FE model with Yeoh’s strain energy density function showed good agreement with experimental results. Finally, In order to study the mechanical behaviour of filler concentrations outside the reliable printing zone, empirical models were developed. These empirical models can predict the tensile strength of the nanocomposite based on filler concentration and the material viscosity. The findings of this research give an insight into the mechanical characterisation and modelling of the 3D printed particulate nanocomposites using photopolymer extrusion technique.
Keywords: 3D printing; Photopolymer extrusion; Nanocomposites; Modelling